2022
DOI: 10.3354/meps14169
|View full text |Cite
|
Sign up to set email alerts
|

Two-way habitat use between reefs and open ocean in adult greater amberjack: evidence from biologging data

Abstract: We investigated the relationships between vertical movements and both oceanographic features and physiological factors in greater amberjack Seriola dumerili, which is a reef-associated predator in the East China Sea. S. dumerili in the coastal waters of eastern Taiwan were equipped with archival tags or pop-up satellite archival tags that recorded depth and temperature, resulting in a dataset covering a total of 1331 d from 12 individuals. To classify the vertical movement patterns of S. dumerili, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…An increase in epibenthic life could lead to increases in smaller fishes that would increase foraging opportunities for predatory fishes. Higher vertical structure could be advantageous for greater amberjack (Tone et al, 2022) and red snapper (Williams-Grove and Szedlmayer, 2017; Bacheler et al, 2021) as both species have been observed making daily vertical movements, thought in part to do with increased forging opportunities. However, our observed selection in red snapper could also be an artifact of where they were tagged; seven of our nine snapper were tagged at the vessel where the probability of remaining at the vessel during 1-hour intervals was 0.96 despite some individuals displaying a clear ability to move among structures.…”
Section: Habitat Usementioning
confidence: 99%
“…An increase in epibenthic life could lead to increases in smaller fishes that would increase foraging opportunities for predatory fishes. Higher vertical structure could be advantageous for greater amberjack (Tone et al, 2022) and red snapper (Williams-Grove and Szedlmayer, 2017; Bacheler et al, 2021) as both species have been observed making daily vertical movements, thought in part to do with increased forging opportunities. However, our observed selection in red snapper could also be an artifact of where they were tagged; seven of our nine snapper were tagged at the vessel where the probability of remaining at the vessel during 1-hour intervals was 0.96 despite some individuals displaying a clear ability to move among structures.…”
Section: Habitat Usementioning
confidence: 99%
“…For instance, a study with an acoustic telemetry device provided movement data of various commercially important fish species, such as Atlantic cod (Gadus morhua; Cote et al, 1998) and winter flounder (Pseudopleuronectes americanus; DeCelles & Cadrin 2010). In the case of pelagic fish study, satellite mediated telemetry system provides a broad movement scale of large fish kinds of Bluefin tuna (Thunnus thynnus; Block et al, 1998) and greater amberjack (Seriola quinqueradiata; Tone et al, 2022). Furthermore, monitoring fish swimming behavior has the potential to enhance the quality of products in the aquaculture industry.…”
Section: Introductionmentioning
confidence: 99%
“…• Whitetip shark (Carcharodon longimanus)(Howey et al, 2016) • Greater amberjack (Seriola dumerili)(Tone et al, 2022) Body temperature Body or visceral warming • Behavioral thermoregulation study on leopard shark (Triakis semifaciata)(Hight & Lowe, 2007) • Feeding ecology study on bluefin tuna (Thunnus maccoyii)(Bestley et al, 2008) Global Positioning System (GPS) for high accuracyLocation• GPS-bouy on sunfish (Mola mola)(Sims et al, 2009) and New Zealand eagle ray (Riding et al• First DO from bluntnose sixgill sharks (Hexanchus griseus)(Coffey & Holland 2015) • PSAT-TDR-DO blue marlin (Makaira nigricans) and sailfish (Istiophorus platypterus)(Logan et al, 2022) ARGOS, Advanced Research and Global Observation Satellite.https://doi.org/10.47853/FAS.2023.e62https://www.e-fas.org | 701…”
mentioning
confidence: 99%